Penguatan Digital Economy Melalui Food Vlogging dalam Promosi Wisata Kuliner Tradisional di Pasar Slumpring Tegal - Didi Pramono; Kuncoro Bayu Prasetyo; Noviani Achmad Putri; Khasan Setiaji; Saufa Alina Alfasya; Gayyutri Naylacitra; Ziryu Robben Duta Wijaya (Madani : Indonesian Journal of Civil Society, 2026)
This community service program was initiated in response to the stagnation of tourist visits to Pasar Slumpring and the limited digital competence of the local tourism awareness group (Pokdarwis) in utilizing social media as a promotional tool. The program aims to strengthen the community’s digital economy through the development of food  vlogging content as a medium for promoting traditional culinary tourism. The implementation employed a Participatory Rural Appraisal (PRA) approach, involving community members in planning, training, content production, and evaluation. The program included a social media workshop, food vlogging training, and digital promotion assistance. The results demonstrate a significant improvement in participants’ digital literacy, with the average score increasing from 44.25 (pre-test) to 80.75 (post-test), indicating an 82.4% enhancement. The food vlogging content produced successfully reached a wide audience, achieving 31,000 views on Instagram and 386,000 views on TikTok. The impact is further reflected in the rise in tourist visits, from 1,217 visitors in August to 1,826 in September (an increase of 50.04%), and continued to grow to 58.25% by November. This program has proven effective in enhancing the digital capacity of Pokdarwis and strengthening digital economy–based promotional strategies. Therefore, the initiative contributes to the development of traditional culinary tourism and supports the achievement of SDGs 8, 9, and 11 on decent work, industrial innovation, and sustainable communities.